The Impact of Smartboard on Preparatory Year EFL Learners’ Motivation at a Saudi University - Ahmad, Waqar; Zuraina, Ali; Sipra, Muhammad Aslam; Taj, Imtiaz Hassan (Australian International Academic Centre, Australia, 2017)
Smartboards, which are now widely used in the teaching and learning process in Saudi Arabia, have turned the traditional environments of the classrooms, especially the EFL classrooms to be more interesting and encouraging. Literature reviews suggest that Saudi students usually lack motivation for studying English as a foreign language. This study tends to investigate the impact of Smartboards on preparatory year EFL learners motivation at a Saudi university. Two intact groups were selected, in which one was termed as experimental and the second as control group. The experimental group was taught using the Smartboard while the control group was taught with the traditional whiteboard, pen and book method. The treatment was given for seven weeks. A questionnaire was administered to both the groups at the beginning and the end of the study. The data was analysed using the SPSS and the results showed that there was significant difference between the experimental and control groups in terms of motivation.